A tree is nice - Udry, Janice May.; Simont, Marc ([New York] : HarperCollins, 1984)
A poetic depiction of the beauty of trees and why they are so good to have around.
Book Links (A.L.A.).
Caldecott Medal/Honor.
Wilson's Children.
Book Links (A.L.A.), June 2001.
Booklist, October 2008.
Horn Book, February 2002.
Keywords: Trees -- Juvenile literature; Trees; Trees